2020
DOI: 10.1007/s40520-020-01699-6
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in COVID-19: epidemiology and clinical correlations in a large group of patients admitted to an academic hospital

Abstract: Background Delirium incidence and clinical correlates in coronavirus disease-19 (COVID-19) pneumonia are still poorly investigated. Aim To describe the epidemiology of delirium in patients hospitalized for suspect COVID-19 pneumonia during the pandemic peak in an academic hospital of Northern Italy, identify its clinical correlations and evaluate the association with mortality. Methods The clinical records of 852 patients admitted for suspect COVID-19 pneumonia, defined as respiratory symptoms or fever or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
77
3
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 32 publications
13
77
3
10
Order By: Relevance
“…The finding that dementia, pre‐existing comorbidity and pulmonary opacity were significantly associated with delirium on admission was somewhat expected according to previous literature 5,26,27 . However, a recent study found that age, history of epilepsy, antipsychotic drugs, vasodilators, urea and lactate dehydrogenase, but not dementia and comorbidity were associated with delirium 15 . The present study, thus, adds knowledge in this field.…”
Section: Discussionsupporting
confidence: 86%
“…The finding that dementia, pre‐existing comorbidity and pulmonary opacity were significantly associated with delirium on admission was somewhat expected according to previous literature 5,26,27 . However, a recent study found that age, history of epilepsy, antipsychotic drugs, vasodilators, urea and lactate dehydrogenase, but not dementia and comorbidity were associated with delirium 15 . The present study, thus, adds knowledge in this field.…”
Section: Discussionsupporting
confidence: 86%
“…Although most previous studies of neurological manifestations of COVID-19 7 did not systematically evaluate patients for delirium despite the availability of validated monitoring tools, one small ICU study reported a delirium prevalence of 84%, 12 whereas a delirium prevalence of 11–12% has been reported among the general population of hospitalised patients with COVID-19. 18 , 19 Although the true prevalence of delirium in critically ill patients with COVID-19 is unknown, patients with COVID-19 are at high risk of delirium due to systemic inflammation and neuroinflammation, other organ system failures, increased risk of thrombosis, and the effects of deep sedative strategies, prolonged mechanical ventilation, and social isolation from families. 12 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…In future months, psychiatrists foresee increased rates for depression and anxiety syndromes. About 11% of Covid-19 cases have delirium ( 55 ). These are older patients with neuropsychiatric comorbidities and worse respiratory conditions.…”
Section: Clinical Findings: a Glance From The Specialistsmentioning
confidence: 99%